2019
DOI: 10.1007/s12144-019-00189-x
|View full text |Cite
|
Sign up to set email alerts
|

Dehumanization after terrorism: the role of psychophysiological emotion regulation and trait emotional intelligence

Abstract: In recent years, numerous terrorist attacks have been perpetrated, inducing a reaction even in people who were not directly exposed. In this scenery, we measured people's blatant dehumanization of Arabs in the aftermath of the attack that took place in Manchester, UK in 2017. The goal of the present work was to assess how dehumanization of a whole group blamed for the attack was influenced by physiological regulation and trait emotional intelligence (trait EI). Further, we measured how this relation changed ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Instead, for ineffective regulators, the increased number of protective behaviours was related to their risk perception. This finding is consistent with the literature on emotion regulation and how people react to real-life emotionally loaded events (e.g., terrorist attacks; Scrimin & Rubaltelli, 2019), although it was reported for the first time in relation to a global pandemic. Importantly, emotion regulation was not associated with a lower risk perception as it was found in other contexts.…”
Section: Discussionsupporting
confidence: 92%
“…Instead, for ineffective regulators, the increased number of protective behaviours was related to their risk perception. This finding is consistent with the literature on emotion regulation and how people react to real-life emotionally loaded events (e.g., terrorist attacks; Scrimin & Rubaltelli, 2019), although it was reported for the first time in relation to a global pandemic. Importantly, emotion regulation was not associated with a lower risk perception as it was found in other contexts.…”
Section: Discussionsupporting
confidence: 92%
“…Leveraging a novel face-morphing method (Figure 2), researchers provided new evidence for outgroup dehumanization, finding that participants were faster to attribute mind to face morphs varying on a continuum from inanimate to fully human when those morphs were based on ingroup (versus outgroup) faces [14] (but see Study 3). Other work has used neuroimaging and measures of heart rate variability to better identify the neural and physiological underpinnings of dehumanization, respectively [11,[15][16][17][18]. Researchers have also developed psycholinguistic dictionaries and computational methods to investigate subtle dehumanization in natural language (e.g., describing targets using fewer words related to agency and experience [19][20][21][22]).…”
Section: Methods and Conceptualizationsmentioning
confidence: 99%
“…It has been shown by several studies that EC modulates risk perception and the estimates of future negative or positive events. For example, people with low EC showed a stronger relation between more negative emotions and the belief that future terrorist attacks would occur in their small town rather than in farther locations, with a greater tendency to see immigrants as threatening [ 21 , 22 ]. Furthermore, it was demonstrated that EC moderates the relation between knowledge and decision making related to food.…”
Section: Introductionmentioning
confidence: 99%